A Philosophical Interpretation of Albert Camus’s Postmodernist Literary Endeavor in The Stranger (1942) - Chouib ,Mohammed; Bentahar ,Soumia (Faculty of Letters and Foreign Languages Department of English, 2023)
This dissertation uses a philosophical framework to understand the postmodernist literary endeavor of the French philosopher, Albert Camus (1913-1960), in his acclaimed novel, The Stranger (1942). Since Camus’s book has been abundantly and excessively read as an existentialist work of fiction, the current dissertation, however, chooses to use an interdisciplinary approach that seeks to understand the novel’s postmodern dimension. Through the lens of the philosophical triad of Derrida, Foucault, and Baudrillard, this dissertation explores how Camus employs postmodern literary techniques in The Stranger to deconstruct meaning, challenge power dynamics, and blur the lines between fiction and reality. While Camus’s philosophy is often situated within modernism, The Stranger exhibits numerous postmodern qualities that point to Camus’s prescience as a writer on the cusp of a new era in literature. In bringing these three postmodern philosophical strands together through a close reading of The Stranger, this dissertation has shed new light on Camus as a postmodern thinker. His blending of existential philosophy with postmodern storytelling techniques has subtly yet profoundly revolutionized narrative form and pointed the way toward the radically fragmentary and self-referential literature that would emerge in the late twentieth century.